Synthesis, Characterization, and Biological Evaluation of New Hg(II) Complexes of (2-(2-(2-chlorobenzylidene)hydrazineyl)benzothiazole with Phosphine Ligands - Alaa Ali; Ahmed Irzoqi; Pramod Singh (Tikrit Journal of Pure Science, 2024)
The Synthesis of new Hg(II) complexes of (2-(2-(2-chlorobenzylidene) hydrazinyl)benzothiazole) (CHB) with phosphine ligands (dppm, dppe, dppp, and dppb) were synthesized, resulting in complexes with the following formulas: [Hg2(CHB)2(µ-dppm)2]Cl4 or [Hg2(CHB)2(µ-phosphine)Cl2]Cl2 (where the phosphines are dppe, dppp and dppb). The suggested geometry around the metal ion is tetrahedral, with the (CHB) ligand acting as a bidentate ligand through the N atoms, while the phosphine ligands act as bidentate bridging ligands through the P atoms. The prepared complexes were characterized various analytical techniques including molar conductivity, infrared spectra, 31P{1H}-NMR, 1H-NMR, and 13C-NMR spectra. Additionally, the biological effectiveness of these  complexes was evaluated against four types of bacteria, namely Streptococcus faecalis,  Staphylococcus aureus,  Escherichia coli and Pseudomonas aeruginosa, has been assessed. Some of the complexes exhibited an inhibition level in the range of (5-10 mm) at the minimum inhibitory concentration indicating potential antibacteria properties.